Gender differences in income among psychiatrists in China: Findings from a national survey - Han, Xinxin; Shen, Lijun; Tong, Jiayu; Jiang, Feng; Liu, Huanzhong; Zhu, Jiming (Frontiers in Public Health, 2022)
Background: Gender income disparity in healthcare settings is a longstanding issue around the globe, but such evidence among Chinese physicians is scarce. This study investigated whether gender income differences exist among physicians in China. Methods: Data came from the 2019 national survey data of 4,520 psychiatrists in major public psychiatric hospitals across China. Self-reported monthly income after tax (in Chinese Yuan, CNY) by participants at all professional ranks was assessed. Average monthly income by gender was reported. Adjusted income differences between male and female psychiatrists were examined using multivariable regression models, adjusting with inverse probability of treatment weights and controlling for physician demographics and hospital fixed effects. Results: The unadjusted mean difference in monthly income after tax by gender was 555 CNY (about $86; 95% CI, -825 to -284; mean [SD] for men: 8,652 [4783] CNY and for women: 8,097 [4350] CNY) in all psychiatrists. After regression adjustments, the income difference by gender among all psychiatrists reduced substantially and became insignificant. However, gender income difference was still observed among senior-level psychiatrists, where female psychiatrists earned 453 CNY (about $70; 95% CI, -810 to -95) significantly less than male psychiatrists. Conclusions: China achieved gender equity in income for psychiatrists overall, the observed income differences among senior-level physicians, however, reveal the persistence of gender inequity at the highest level of professional hierarchy. These findings call for policy attention to the issue of gender income disparity among physicians in China’s healthcare system.